2019
DOI: 10.1037/law0000196
|View full text |Cite
|
Sign up to set email alerts
|

Communicating violence risk during testimony: Do different formats lead to different perceptions among jurors?

Abstract: The legal system often charges forensic clinicians with the task of assisting the court in making decisions about a defendant's risk for violence. The extent to which these evaluations are useful depends, in part, on how the results are communicated to and understood by the trier of fact. Using a sample of 155 participants who previously served as a criminal trial juror, this study examined the effects of various risk communication formats on participants' perceptions of a hypothetical defendant's risk level, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 57 publications
1
12
0
Order By: Relevance
“…Available in Online Supplemental Materials is an Appendix containing the two actuarial tools along with the experience tables intended for field use. Their designs were informed by the recommendations of an expert consensus group (Trevena et al, 2013) and are supported by empirical findings across diverse contexts (Aakl et al, 2011;McDowell & Jacobs, 2017;Zipkin et al, 2014), such as communication of violence risk (Batastini et al, 2019), health-related information (Buchter et al, 2014;Fagerlin et al, 2011;West et al, 2013), and weather forecasts (Joslyn & LeClerc, 2012).…”
Section: Final Actuarial Toolsmentioning
confidence: 99%
“…Available in Online Supplemental Materials is an Appendix containing the two actuarial tools along with the experience tables intended for field use. Their designs were informed by the recommendations of an expert consensus group (Trevena et al, 2013) and are supported by empirical findings across diverse contexts (Aakl et al, 2011;McDowell & Jacobs, 2017;Zipkin et al, 2014), such as communication of violence risk (Batastini et al, 2019), health-related information (Buchter et al, 2014;Fagerlin et al, 2011;West et al, 2013), and weather forecasts (Joslyn & LeClerc, 2012).…”
Section: Final Actuarial Toolsmentioning
confidence: 99%
“…From a policy and practice perspective, generating base rates for predictors of violent extremism in a general population sample will help develop more rigorous putative risk and protective factors , increase transparency in the provision of evidence , reduce potential bias in decision‐making (, however, see Ref. ), improve risk communication , and allow for risk assessments based on Bayesian principles . Knowledge of base rates could also inform different forms of risk and threat assessment differently, as well as guide risk management and intervention (see Discussion).…”
mentioning
confidence: 99%
“…Overall, risk management information and categorical representation of risk were associated with higher ratings of risk. Though previously risk management information was found to aid judges in their decisions (Dolores & Redding, 2009), this study found the inclusion led to more severe overestimations of risk (Batastini et al, 2019).…”
Section: Comparing Risk Communication Strategiesmentioning
confidence: 60%
“…Research also suggests that risk management and categorical presentations of risk without actuarial data produce higher risk estimates, and that the inclusion of visual aids to contextualize base rates seems to be ineffective. Numerical presentations by experts in the courts may not be understood by laypersons and it may be beneficial to provide data driven examples to support a categorical risk estimate (Batastini et al, 2019). The research also suggests that in accordance with findings from cognitive psychology, laypeople tend to ignore base rates when making decisions.…”
Section: Comparing Risk Communication Strategiesmentioning
confidence: 69%
See 1 more Smart Citation